Химия коллоидов и нанопорошков: учебное пособие - Ильин А. П. Александр Петрович; Мирошниченко Ю. Ю. Юлия Юрьевна; Роот Л. О. Людмила Олеговна; Коршунов А. В. Андрей Владимирович (Томск, Изд-во ТПУ, 2013)
Заглавие с титульного экрана